Pulmonary tuberculosis in the immunocompromised patients - Vukosav Danijela; Tot-Veres Kristina (Vojnosanitetski Pregled)
Background/Aim. During the last few decades, immunocompromising diseases led to an increase in the number of tuberculosis cases. The aim of this study was to examine the influence of immunocompromising diseases on the course of tuberculosis. Methods. The research included two groups, each consisting of 40 subjects with tuberculosis, who were treated at the Institute for Pulmonary Diseases of Vojvodina during 2010 and 2011. The first group had no immunocompromising diseases (the kontrol group), whereas the second group contained patients with accompanying immunocompromising diseases. The data from the patients’ medical history, from the Center for Microbiology and from the Radiology Center were used. The two groups were compared according to the following characteristics: age, sex, bacteriological status, radiological presence of the disease, presence of adverse effects of drugs, presence of resistance to drugs, duration of the therapy regimen and the duration of hospitalization. Results. The group of immunocompromised patients was older in average than the control group and included a higher percentage of males. The immunocompromised group had statistically important longer average time required for the sputum smear conversion (p = 0.000) and for the conversion of sputum cultures to M. tuberculosis (p = 0.010), more frequent presence of cavity (p = 0.030), longer average therapy regimen duration (p = 0.000) and higher average number of hospital days (p = 0.000) compared to the control group. The most frequent localization of changes in the immunocompromised patients was in all lobes of both lungs (32.5%) whereas the changes in the control group were mostly localized in the upper lung lobes (62.5%). There was no statistically important difference in the finding of sputum smear positive acidfast bacilli on direct micoscropy, the presence of adverse effects of drugs and M. tuberculosis resistance to drugs between the two groups of patients. Conclusion. The immunocompromising diseases change the course of tuberculosis, primarily by affecting bacteriological status, radiological presentation, the length of therapy regimen and the duration of hospitalization.